2021
DOI: 10.3390/ijms22084229
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota Affects Corticosterone Production in the Murine Small Intestine

Abstract: Glucocorticoids (GCs) are hormones that are released in response to stressors and exhibit many activities, including immunomodulatory and anti-inflammatory activities. They are primarily synthesized in the adrenal gland but are also produced in peripheral tissues via regeneration of adrenal 11-oxo metabolites or by de novo synthesis from cholesterol. The present study investigated the influence of the microbiota on de novo steroidogenesis and regeneration of corticosterone in the intestine of germ-free (GF) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…The detection of CORT in the bullfrogs GIT agrees with previous studies showing GIT CORT production in mammals, which suggests that anuran's GIT tissue can produce glucocorticoids as well (Ergang et al, 2021; Kostadinova et al, 2014). However, bullfrog's GIT CORT levels did not increase after contaminated meal intake.…”
Section: Discussionsupporting
confidence: 90%
“…The detection of CORT in the bullfrogs GIT agrees with previous studies showing GIT CORT production in mammals, which suggests that anuran's GIT tissue can produce glucocorticoids as well (Ergang et al, 2021; Kostadinova et al, 2014). However, bullfrog's GIT CORT levels did not increase after contaminated meal intake.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, HK-LRCC5314 treatment suppressed corticosterone secretion in mice. Corticosterone, a major hormone induced as a stress response and stress mediator, plays a key role in insulin resistance signaling, intestinal inflammatory response, and T2D via stressors [ 59 , 60 ]. In addition, combination of chronic stress exposure and HFD showed increased corticosterone secretion accompanied by elevated HPA activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, combination of chronic stress exposure and HFD showed increased corticosterone secretion accompanied by elevated HPA activity. These conditions were associated with alternation of intestinal bacterial composition and intestinal inflammatory markers [ 60 ]. Previous studies have demonstrated that heat-killed L. casei DKGF7 and L. paracasei treatment reduced serum corticosterone levels along with low inflammatory cytokines in intestine in murine models [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential psychobiotic, Bifidobacterium longum 1714, reduces reported stress and attenuates increases in stress-induced salivary cortisol in healthy volunteers (9). Further, intestinal corticosterone production in response to stress is reduced in germ-free mice (63).…”
Section: Corticosteroidsmentioning
confidence: 99%